Perception about Dental Myths among General Public - P S Gayathri; Krithika C; R Hema Maheshwari; Jasti Keerthi; Jenisha Priyavadhani S; Harshada Ragunathan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Myths are part of everyone’s life. Considering the outcomes of beliefs, one should be awareabout the myths about health care as it may result in outrageous complication. Certain culture and culturalbeliefs have a greater impact in health and sickness which represents different ideas shared by differentpeople in India.Aim: This study was aimed to assess the knowledge about dental myths among general public, in TamilNadu.Methodology: A cross sectional study was conducted using self-administered questionnaire, through Googleforms, among 200 people from the age group of 17-54 years in Tamil Nadu, India. Statistics was done andtabulated.Results: Most of the participants were not having adequate awareness and knowledge about dental myths.Conclusion: Thus, awareness and knowledge about dental myths among general public has to be improvedby community oral health programs.